Smartphones and social media as status symbol of Gen Z - Szabó, Dóra; Dani, Erzsébet (Folia Toruniensia, 2022)
Smartphones have led to the formation of new habits and behavioral patterns and are the most widespread infocommunication tool today. They also appear as status symbols among the Z and Alpha generations. This tool performs an important role in the lives of the younger generation and impacts social media platforms; which has led to further questions. This is a particularly important topic nowadays because the area of media awareness does not only refer to the family, but also encompasses educational institutions that contribute to the promotion of conscious use of the media. A PILOT survey was used with the goal of mapping out how students relate to their phones. This survey was the right choice because it is one of the cornerstones of education for proper media behavior and critical thinking. In the course of the research, I asked young people aged 13-19 what they thought about status symbols, how they related to their smartphones, what role they took on social media when they encounter a multitude of influencers.